Answer:
[tex]y-(-1)=-\frac{2}{7}(x-(-4))[/tex]
Step-by-step explanation:
We know that the line passes through (-4,-1) and (3,-3), where [tex](x_{1} ,y_{1} )[/tex] is [tex](-4,-1)[/tex] and [tex](x_{2} ,y_{2} )[/tex] is [tex](3,-3)[/tex].
First, we need to find the slope with the formula
[tex]m=\frac{y_{2}-y_{1} }{x_{2}-x_{1} }[/tex]
Replacing given points
[tex]m=\frac{-3-(-1)}{3-(-4)}=\frac{-3+1}{3+4}=\frac{-2}{7}[/tex]
Then, we use the slope, one point and the slope-point form
[tex]y-y_{1} =m(x-x_{1} )\\y-(-1)=-\frac{2}{7}(x-(-4))\\ y+1=-\frac{2}{7}x+\frac{8}{7} \\y=-\frac{2}{7}x+\frac{8}{7}-1\\y=-\frac{2}{7}x+\frac{8-7}{7} \\y=-\frac{2}{7}x+\frac{1}{7}[/tex]
The slope-intercept form is
[tex]y=-\frac{2}{7}x+\frac{1}{7}[/tex]
The point-slope form is
[tex]y-(-1)=-\frac{2}{7}(x-(-4))[/tex]